anonymous
  • anonymous
Use the demoivre's theorem to find the answer? (1+i)^8
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Let \(z=1+i\) then: \[\left| z \right|=\sqrt{1^2+1^2}=\sqrt 2; \theta= \tan^{-1}({1 \over 1})=\pi/4\]. Writing z in polar coordinates: \[z=\sqrt2 (\cos({\pi \over 4})+i \sin({\pi \over 4}))\]. Now apply demoivre's theorem: \[(1+i)^8=z^8=(\sqrt{2})^8(\cos(8{\pi \over 4})+i \sin(8{\pi \over 4}))=2^4(\cos(2\pi)+i \sin(2\pi))=16(1+i (0))=16\]
anonymous
  • anonymous
By the way, you can easily prove this by simple calculation: \[(1+i)^8=[(1+i)^2]^4=(1+2i+i^2)^4=(2i)^4=2^4(i^4)=16\] Notice here that \(i^2=-1\) and \(i^4=1\).
anonymous
  • anonymous
what if the question is (1-i)^11

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
Try to follow the same procedure and tell what you get.
anonymous
  • anonymous
what to do after this step 2(under root )^11 (cos-11/4+isin-11/4)
anonymous
  • anonymous
sorry cos-11pie/4+isin-11pie/4
anonymous
  • anonymous
\(cos (-11\pi/4)=sin(-11 \pi/4)=1/\sqrt2\)
anonymous
  • anonymous
sorry \(-1/\sqrt2\)
anonymous
  • anonymous
but how???
anonymous
  • anonymous
\[\cos({-11 \pi \over 4})=\cos(4\pi-{11\pi \over 4})\cos({5\pi \over 4})\]. \(5\pi/4\) is the correspondent angle of \(pi/4\) in the third quadrant, Hence cos\((-11\pi/4)=-1/\sqrt2\).
anonymous
  • anonymous
There is a missing equality in the first line between the two cosines :)

Looking for something else?

Not the answer you are looking for? Search for more explanations.